Demographic Characteristics Influence Treatment Costs of Invasive Melanoma in Florida. Issue 3 (March 2023) - Avila, Francisco R.; Spaulding, Aaron C.; Rinker, Brian D.; Huayllani, Maria T.; Boczar, Daniel; Torres-Guzman, Ricardo A.; Maita, Karla C.; Ho, Olivia A.; Forte, Antonio J.
Abstract : Background: Demographic characteristics are known to influence the treatment and outcomes of patients with invasive melanoma. Whether these characteristics influence treatment costs is unknown. We aimed to analyze whether patient demographics and tumor characteristics influence treatment costs for patients with invasive cutaneous melanoma in Florida. Methods: This was a cross-sectional study in which the Florida Inpatient and Outpatient Dataset of the Agency for Health Care Administration was analyzed for patients with a diagnosis of invasive melanoma between January 1, 2013 and December 31, 2018. Categorical variables were assessed using Pearson χ 2 tests, and continuous variables were evaluated using Kruskal-Wallis tests. Logistic regression analysis was conducted to identify the association between patient demographics and total costs. All analyses were done using SAS 9.4 statistical software (SAS Institute, Inc). Results: Multivariate analysis showed that sex ( P < 0.001), hospital setting ( P < 0.001), race/ethnicity ( P < 0.01), patient region ( P < 0.01), Elixhauser Comorbidity Index score ( P < 0.001), presence of metastasis ( P < 0.01), total number of procedures ( P < 0.001), and length of stay ( P < 0.001) were correlated with the cost of treatment of invasive cutaneous melanoma. After stratification, the association between cost and race/ethnicity disappeared for inpatients but remained for Black patients in the outpatient setting ( P < 0.001). The association between cost and patient residence regions also differed when the cohort was stratified. Conclusions: Strategies addressing disparities in treatment cost of invasive melanoma should differ, depending on the hospital setting where the patient is being treated.